Improving Work Discipline, Work Facilities, and Job Satisfaction to Support Employee Performance at PT. Cahaya Cipta Makmur - Karina, Carreyra Cucu; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The activity program at PT. Cahaya Cipta Makmur was carried out to identify and overcome various problems faced by the company, such as the lack of formal work regulations, the absence of SOPs in the production unit, inadequate work facilities, and the unavailability of product catalogs. The objectives of this program are to improve the operational work structure, maintain product quality, and improve the product information system to consumers. The results of this activity include the preparation of work regulations, the creation of SOPs, the provision of work equipment, the creation of product catalogs, and the measurement of job satisfaction and employee performance, all of which have been successfully implemented in accordance with the predetermined plan.